PEMBELAJARAN KOOPERATIF SFAE DAN CIRC UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP - Gemita Lumunon; Sonya Tauran (LPPM Universitas Advent Indonesia, 2021)
This comparative design study aims to find out how to improve student’s mathematical communication skills using cooperative learning models and Student Facilitator and Explaining (SFAE) and Cooperative Integrated Reading and Composition (CIRC) type, and to find out whether there are differences between the two. The sample in this study were students of class VIII C and VIII D in SMP Negeri 3 Parongpong, Bandung Barat. The instrument used in this study was a mathematical communication ability test instrument and a non-test instrument in the form of a response questionnaire. The results showed that increasing mathematical communication skills of students who obtained the cooperative learning model SFAE type and CIRC were categorized as moderate. Statistically, there is no significant difference on mathematical communication ability between students who obtained the SFAE and the CIRC . The results of the questionnaire showed that student’s really liked the cooperative learning model type of SFAE and liked the type of CIRC.